Excursion Tours and the Possibility of using Augmented Reality Technologies for Improving the Local Tourist Attractiveness - BOGOMAZOVA, Irina Victorovna; STENYUSHKINA, Svetlana Gennad’evna (Journal of Environmental Management and Tourism, 2017)
The tourist industry in modern conditions is a multifold sphere demanding a wide variety of information technologies. It concerns both introduction of specialized software packages system for ensuring automation of tourism organization and the use of global computer networks. Implementing of computer technologies in the tourist business and their active application create possibilities of further increase in tourist appeal of the territory. The real stage of development of tourist and recreation activity is bounded with changes in technologies of the mobile excursion projects connected with appearance and introduction of interactive opportunities. The example of this direction is technologies for creating augmented reality, which is a result of the implementing any sensory data to complete information about the environment and improve the perception of information.